Microsoft Excel 2013 inside out - Dodge, Mark (Inside out (Redmond, Wash.), 2013)
This book is packed with hundreds of timesaving solutions, troubleshooting tips, and workarounds. Learn how the experts tackle Excel 2013 - and challenge yourself to new levels of mastery. Topics include: customizing the Excel workspace; best practices for designing and managing worksheets; creating formulas and functions; performing statistical, what-if, and other data analysis; core to advanced charting techniques; using graphics and sparklines; managing databases and tables; automating Excel with macros and custom functions; collaborating in Excel online, in the cloud, and more; extending Excel. --